2010
DOI: 10.1016/j.ophtha.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Sensation and Subbasal Nerve Alterations in Patients with Herpes Simplex Keratitis

Abstract: Purpose-To study and correlate corneal sensation in patients with herpes simplex keratitis (HSK) with density and morphology of subbasal corneal nerves by in vivo confocal microscopy (IVCM).Design-Prospective, cross-sectional, controlled, single-center study.Participants-Thirty-one eyes with the diagnosis of acute (n=7) or chronic (n=24) HSK and the contralateral clinically unaffected eyes were studied and compared to normal controls (n=15). (Confoscan 4, Nidek) and corneal esthesiometry (Cochet-Bonnet) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
244
2
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(269 citation statements)
references
References 30 publications
14
244
2
9
Order By: Relevance
“…[10][11][12][13] Furthermore, in addition to providing trophic and sensory functions, corneal nerves have been shown to play an important role in the maintenance of ocular surface epithelial health and function. [14][15][16][17] As epithelial DCs and subbasal nerves may change in a variety of ocular surface and corneal conditions, such as dry eye disease, neurotrophic keratopathy, infectious keratitis, diabetes, and contact lens wear, 3,5,[18][19][20][21][22] quantification of these two structures, which can be achieved by IVCM, is of significant importance. The high resolution of IVCM images is inherently associated with a drawback, which is a relatively small field of view of the images.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] Furthermore, in addition to providing trophic and sensory functions, corneal nerves have been shown to play an important role in the maintenance of ocular surface epithelial health and function. [14][15][16][17] As epithelial DCs and subbasal nerves may change in a variety of ocular surface and corneal conditions, such as dry eye disease, neurotrophic keratopathy, infectious keratitis, diabetes, and contact lens wear, 3,5,[18][19][20][21][22] quantification of these two structures, which can be achieved by IVCM, is of significant importance. The high resolution of IVCM images is inherently associated with a drawback, which is a relatively small field of view of the images.…”
Section: Purposementioning
confidence: 99%
“…In vivo confocal microscopy imaging was performed by a method previously described in detail. 21 In brief, the distance from the cornea to the microscope was kept stable by a singleuse disposable sterile polymethylmethacrylate cap (Tomo-Cap; Heidelberg Engineering), filled with a layer of the lubricant 2 mg/g carbomer-containing gel (Vidisic gel; Bausch & Lomb, Heidelberg, Germany). Both eyes were instilled with topical anesthesia using Oxybuprocaine hydrochloride 4 mg (Conjuncain EDO; Dr Gerhard Mann Chem.-Pharm.…”
Section: Standard In Vivo Confocal Microscopymentioning
confidence: 99%
“…No significant differences in corneal sensitivity are explained by the fact that abnormal corneal sensitivity is noted with a subbasal nerve density below the threshold of 835 mm per frame. 28 Furthermore, patients with PCG had significantly reduced central corneal thickness and significantly higher density of corneal basal epithelial cells compared with controls. It has been well established that corneal nerves have important trophic effects on epithelial cell growth and proliferation, keratocyte homeostasis, and corneal wound healing.…”
mentioning
confidence: 97%
“…[19][20][21] Rosenberg et al 27 have reported that reduction of subbasal plexus nerve fibers correlates with loss of corneal sensitivity in patients with diabetic neuropathy, while tortuosity of subbasal nerves correlated significantly with the severity of diabetic neuropathy. Hamrah et al 28 have recently described significant morphological changes in corneal subbasal nerve plexus in patients with herpes simplex keratitis and showed that reduction of nerve density correlated significantly with loss of corneal sensitivity in such patients.…”
mentioning
confidence: 99%
“…Although herpetic keratitis (HK) is the entity most consistently implicated in neurotrophic keratopathy and loss of the sub-basal nerve plexus, 3 other infectious disease states may be associated with corneal nerve alterations as well. In Acanthamoeba keratitis (AK) and fungal keratitis (FK), defining corneal nerve involvement on a histopathological level may aid in clarifying the disease processes and in potentially developing novel treatment modalities.…”
Section: Introductionmentioning
confidence: 99%